Functionalized gold nanoparticles improve afatinib delivery into cancer cells. (2nd January 2016) - Coelho, Sílvia Castro; Almeida, Gabriela M; Pereira, Maria Carmo; Santos-Silva, Filipe; Coelho, Manuel AN
Abstract : Objectives: A drug delivery system based on colloidal pegylated gold nanoparticles (PEGAuNPs) conjugated with the tyrosine kinase inhibitor afatinib was designed and tested for enhancing the drug activity against pancreatic and NSCLC cells. Methods: PEGAuNPs were synthesized and characterized physicochemically. Confocal imaging was performed to evaluate the nanoparticle (NP) internalization in cancer cells. For cell-cycle distribution analysis, conjugated NPs and afatinib alone were incubated with cells and alterations on the cell-cycle profile subsequently analyzed by total DNA staining. Cancer cell survival and growth inhibition following incubation with afatinib and PEGAuNPs–afatinib (concentrations between 0.007 and 0.500 µM afatinib) were evaluated. Results: A higher cellular uptake of PEGAuNPs was observed by cancer cells. Our data suggest an efficient conjugation of PEGAuNPs with the drug, enhancing the afatinib activity in comparison with afatinib alone. In fact, IC50 and GI50 results obtained show that the PEGAuNPs–afatinib conjugate is ca. 5 and 20 times more potent than afatinib alone in S2-013 and A549 cell lines, respectively. Conclusions: Conjugating PEGAuNPs with afatinib is a promising antitumor delivery system for cancer therapy as it improves drug efficacy, allowing a reduction in drug dose used and minimizing possible toxicity-related side effects.